(untitled) (Práxis Educativa, 2024)
The study analyzes the perceptions that university and secondary teachers have about formative assessment, the use of ICT and the curricular articulation present in the philosophy pedagogy career and philosophy courses in the school system in Chile. The research is qualitative and is based on the implementation of focus groups. Philosophy pedagogy teachers from a Chilean university and teachers from private subsidized middle or secondary education centers participated in this process. The results of this research shed light on the similarities and discursive tensions that exist between the different actors in the field of university and secondary education around formative assessment, technology and curricular articulation. Keywords: Formative assessment. ICT. Curriculum Articulation.